Local participatory innovations and experts as political entrepreneurs: The case of China's democracy consultants. Issue 3 (15th April 2016) - Almén, Oscar
Abstract : This study is concerned with understanding the dynamic behind participatory innovations in China. The case of China provides a contrast to the literature on participatory innovations in democracies. While participatory innovations in democratic countries are seen as a way to deepen and improve democracy, in China these innovations are to some extent developed in order to provide an alternative to electoral democracy. In this article I introduce the concept democracy consultant to describe expert political entrepreneurs involved in the development of participatory innovations. Research on local participatory innovation in China is abundant but the role that experts play in this process has previously not been analysed. Based on in-depth interviews with democracy consultants and local officials, the study finds that democracy consultants frequently act as bridges between central and local levels of government by providing expertise, information, legitimacy, and connections. This is especially true in localities where local leaders want to gain the attention of the central level but lack the required expertise and connections.